Synthesis of ZrO2 nanoparticle and design of HEMT devices. Issue 176 (21st November 2016) - Subash, T. D.; Gnanasekaran, T.; Freeda, M.
ABSTRACT: Zirconium dioxide nanoparticles were synthesized at room temperature. The Characterization of ZrO2 nanoparticles were expressed by X-ray Diffraction. Using this, the size of the nanoparticle is analysed. Structural Characterization is performed using SEM. It is found to be 41 nm to 99 nm. The ZrO2 is a high-k dielectric material which is used to design the transistor. For designing purpose the simulator TCAD is used. By which, the HEMT device is structured and its performance is analyzed and it is found to that transistor operates as normal devices. This experimental is more advantageous since nanoscaling factor and high dielectric constant is used in the device.